TEAM-COHESION AS AN ENTREPRENEURIAL CULTURE FOR INNOVATION CAPABILITIES OF SMES IN LAGOS STATE (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2025)
Small and medium-sized enterprises (SMEs) have become a lubricant for socio-economic development and growth of every nation. However, this sector, particularly in developing countries like Nigeria tends to face substantial issues in staying competitive and achieving sustainable growth in today’s fast-evolving markets, where rapid technological advancements and market instability are prevalent. In most cases, people often see innovation challenges of SMEs from constrained resources, limited access to cutting-edge technologies, and insufficient external support. Conversely, adequate attention has not been given to relational and entrepreneurial capacity of SMEs that can engender collaborative efforts towards innovation enhancement. The study, therefore, leverages Belbin’s team roles theory to examine team-cohesion as an entrepreneurial culture for innovation capabilities of SMEs in Lagos State. Cross-sectional and random sampling techniques were deployed to gather data from 403 SME owners/Operators in Lagos State from the population of 8,395 out of which 385 were validly filled and returned through the aid of snowballing approach and this is above initial 382 sample size. The primary data retrieved from the participants were further subjected to statistical analysis with the aid of frequency, Pearson Product Moment correlation coefficient, and regression. The study concludes that team-cohesion as an entrepreneurial culture of SMEs through team risk-taking propensity, collaborative team work, and open communication can significantly foster innovation capabilities of the operators. The study further acclaims that by embedding cohesion into the organizational culture of SMEs, they can drive teams to draw on diverse perspectives and address challenges collectively, which is crucial for driving innovation.